Isozyme analysis of a tropical forest tree, Pterocarpus macrocarpus Kurz - Liengsiri, C.; Yeh, F.C.H.; Boyle, T.J.B. (1995)
Genetic variation within and among 11 natural populations of Pterocarpus macrocarpus Kurz. from different forest habitats in Thailand was examined by starch gel electrophoresis of 18 loci coding for 11 enzymes. The species possesses a high level of isozyme variation. The percentage of polymorphic loci per population ranged from 66.67 to 100% with a mean of 82.32% and the number of alleles per locus per population ranged from 2.44 to 2.94, averaging 2.67. Observed average population heterozygosity, at 0.222, was lower than the expected average population heterozygosity (0.246) and the estimate of FIS, at 0.099, suggests some degree of inbreeding within populations. There was a high degree of among-population differentiation. All 18 loci exhibited allelic heterogeneity and the estimate of FST was 0.12. Cluster analysis revealed an east-west pattern of population grouping, in accordance with significant correlations between allelic frequencies and longitudes at eight loci. The correlation coefficient between genetic and geographic distance at 0.515 (P < 0.0001) suggests that isolation by distance might in part have been a contributing factor to population differentiation in this tropical forest tree.